2022
DOI: 10.1128/mbio.02422-22
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Promiscuity of an Orphan Small Alarmone Hydrolase Facilitates Bacterial Environmental Adaptation

Abstract: Small alarmone hydrolases (SAHs) comprise a widespread family of alarmone metabolizing enzymes. In metazoans, SAHs have been reported to control multiple aspects of physiology and stress resistance through alarmone and NADPH metabolisms, but their physiological functions in bacteria is mostly uncharacterized except for a few reports as antitoxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…In this work, we discover that Aph1 and related proteins function as potent (p)ppApp hydrolases. Prior to our study, six other enzymes had been shown to hydrolyze (p)ppApp: SAH Mex , Dm MESH-1, Hs MESH-1, Pa SAH, ATFaRel, and Xcc SAH ( 13 , 24 26 ). Of these, only SAH Mex specifically hydrolyzes (p)ppApp but it does so at a much lower catalytic rate than Aph1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we discover that Aph1 and related proteins function as potent (p)ppApp hydrolases. Prior to our study, six other enzymes had been shown to hydrolyze (p)ppApp: SAH Mex , Dm MESH-1, Hs MESH-1, Pa SAH, ATFaRel, and Xcc SAH ( 13 , 24 26 ). Of these, only SAH Mex specifically hydrolyzes (p)ppApp but it does so at a much lower catalytic rate than Aph1.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dual activity was also observed for an SAH identified in Xanthomonas campestris pv. campestris , Xcc SAH ( 25 ). In addition to Pa SAH and Xcc SAH, the cognate antitoxin for FaRel, referred to as ATFaRel, degrades both (p)ppGpp and ppApp to protect against FaRel-mediated intoxication ( 13 ).…”
mentioning
confidence: 99%
“…5a). Interestingly, recent 13 studies mention the ability of the Methylobacterium extorquens RSH, B. subtilis SasA and Treponema denticola SAS proteins to synthesize both (p)ppGpp and (p)ppApp [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent paper from Wang lab has confirmed the NADPH phosphatase activities of SAH in phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) and sah loss strongly reduced NADH, showing the evolutionary conservation of the NADPH phosphatase activities across multiple kingdoms [ 33 ].…”
Section: The Relevant Substrate Of Mesh1 Is Revealedmentioning
confidence: 99%
“…In addition, there is also an evolutionary acquisition of distinct substrates of SpoT versus MESH1. During evolution, enzymes may have altered substrate specificity for a new substrate or broader substrate specificity, as shown for the ability of Xcc SAH to hydrolyze both (p)ppGpp and NADPH [ 33 ]. Evolutionary changes in substrate preferences can coincide with the development of new signaling pathways.…”
Section: Implication For Our Understanding Of Stringent Response and ...mentioning
confidence: 99%